An Individual Growth Model Analysis of Childhood Spanking on Change in Externalizing Behaviors During Adolescence: A Comparison of Whites and African Americans Over a 12-Year Period. (October 2018) - Gibson, Chris L.; Fagan, Abigail A.
This study examines the long-term effect of corporal punishment on children's externalizing behaviors, and race differences in this relationship, using 12 years of prospective data from 1, 075 high-risk White and African American families participating in the Longitudinal Studies of Child Abuse and Neglect. According to multilevel individual growth models, there was a significant, positive association between spanking during childhood (measured at ages 4, 6, and 8 years) and initial levels (at age 12 years) of externalizing behaviors for the full sample and for African Americans. The fixed effect of spanking on rates of change of externalizing behaviors during adolescence (i.e., at ages 12, 14, and 16 years) was significant for the full sample and marginally ( p < .10) significant for African Americans, with more spanking resulting in a slower rate of decrease in externalizing behaviors. Spanking was not related to initial levels or rates of change in externalizing behaviors for White youth.